2021–2022 Florida Citrus Production Guide: Citrus Black Spot: Chapter 36, PP279/CG088, rev. 4/2021 - Dewdney, Megan M.; Walker, Callie; Roberts, Pamela D.; Peres, Natalia A. (EDIS, 2021)
Sections: regulatory considerations; growers, caretakers, harvesters, and haulers; processing and packing facilities and haulers, disposal of citrus debris; Interstate shipment of fruit; export shipment of fruit; regulatory remarks; and recommended chemical controls